An Analysis of Language Styles in the Movie “Instant Family” - Ni Kadek Ayu Siska Sinta Dewi; I Made Perdana Skolastika (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study analyzes the language styles in the movie